DYNAMICS OF TRANSFORMATION OF ISLAMIC EDUCATION POLICY IN THE NATIONAL EDUCATION SYSTEM - Anwarudin, Kusoy; Syahril Akbar , Gilang (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The background of this research stems from the important role of PAI in shaping the moral and spiritual character of students in Indonesia, as well as the challenges that PAI policies must adapt to in response to changing times, particularly in the digital era. Purpose: This study explores the transformation of Islamic Religious Education (PAI) policies within Indonesia's national education system, analyzing how these policy changes have responded to evolving social, political, cultural, and economic needs. Method: Through a literature review across different governmental periods, from the Old Order to the Reform Era, this study identifies significant changes in PAI policies influenced by socio-political dynamics. These changes have impacted the implementation of PAI in schools and madrasahs, as well as the development of curricula and teaching methods. Result: The findings highlight the need for PAI policies to be more adaptive to contemporary challenges, especially in the digital age. Conclusion: This study contributes to a deeper understanding of the dynamics of PAI policies and their role in improving the quality of Islamic education in Indonesia.